On the Cauchy problem for two-dimensional systems of linear functional differential equations with monotone operator - Šremr, J.; Hakl, R. (Нелінійні коливання, 2007)
We establish new efficient conditions sufficient for the unique solvability of the Cauchy problem for twodimensional systems of linear functional differential equations with monotone operators.